2014
DOI: 10.9734/bjpr/2014/5998
|View full text |Cite
|
Sign up to set email alerts
|

Dose Response of Viola odorata on Meiotic and Mitotic Chromosomes of Vicia faba

Abstract: This work was carried out in collaboration between all authors. Author MA designed the study, performed the statistical analysis, wrote the protocol, and wrote the first draft of the manuscript. Author AK managed the experimentations, analyses of the study and the literature searches. Both authors have read and approved the final manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…This reduction in mitotic activity could be attributed to inhibition of DNA synthesis or a blocking in the G2 phase of the cell cycle, preventing the cell from entering mitosis (Talukdar, 2013). The depression in MI has been also suggested as a result of physiological changes induced by the extract in nuclear chromatin and chromosomal anomalies resulting in deficiency of nucleic acid and associated proteins (Asthana and Kumar, 2014). In this study, Inhibition of MI in barely dividing cells probably is owing to the mutagenic compounds in the eucalyptus extract through their action on spindle assembly or cell cycle regulators (Dragoeva et al, 2015).…”
Section: Cytotoxicity Assaymentioning
confidence: 64%
See 2 more Smart Citations
“…This reduction in mitotic activity could be attributed to inhibition of DNA synthesis or a blocking in the G2 phase of the cell cycle, preventing the cell from entering mitosis (Talukdar, 2013). The depression in MI has been also suggested as a result of physiological changes induced by the extract in nuclear chromatin and chromosomal anomalies resulting in deficiency of nucleic acid and associated proteins (Asthana and Kumar, 2014). In this study, Inhibition of MI in barely dividing cells probably is owing to the mutagenic compounds in the eucalyptus extract through their action on spindle assembly or cell cycle regulators (Dragoeva et al, 2015).…”
Section: Cytotoxicity Assaymentioning
confidence: 64%
“…The bridges in the cells were probably formed due to breakage and fusion of chromatids or subchromatids. Bridges occurrence could be attributed to chromosomal stickiness, breakage and reunion and unequal translocation or inversion of chromosome segments (Singh, 2002).Vagrants and laggards (rarely noticed in this study), were possibly formed due to the interference of mutagen with spindle apparatus proteins causing inhibition of centromeric and spindle activity, and subsequent failure of chromosomes to move toward either of the poles (Asthana and Kumar, 2014). The presence of bridges, laggards and fragments indicate the clastogenic effects of eucalyptus extract on Hordeum cells.…”
Section: Genotoxicity Assaymentioning
confidence: 84%
See 1 more Smart Citation
“…Our mothers would take small amount or spices and relevant herbs to make the recipe to soothe our pains. It is reported that the inadvisable higher dose of recipe made by plant part poses a definite risk if it contains toxic substances [1]. Spices also enhance the taste of food; deodorize living places, adding a pleasing scent around homes and other spaces.…”
Section: Introductionmentioning
confidence: 99%
“…In a study on novel inflorescence architecture in gamma radiation-induced faba bean mutant populations, the determinant and indeterminant mutants were characterized by Nurmansyah et al (2019) and it was reported that determinant mutants had shorter plant height, earlier maturity, lower biological and seed yield than indeterminant mutants. The potency of gamma radiation on increasing genetic diversity of morphological and agronomical traits was investigated in faba bean and demonstrated the successful program of induced mutagenesis in this species (Nurmansyah et al 2020) The chromosomes of faba bean because of the easy accessibility, big size, small number (2n=12), and recognizable properties are suitable for research purposes such as mutation breeding and studying chromosome anomalies (Sharma et al 2009, Asthana andKumar 2014). Although the application of gamma rays to create a population with a large genetic diversity and access to mutants with appropriate properties has been accepted by researchers, the presence of various chromosomal anomalies in the population is inevitable.…”
mentioning
confidence: 99%